Financial Crises: Systemic or Idiosyncratic - Hyman P. Minsky (Levy Economics Institute of Bard College, 1991)
The presentations at this conference are by economists from Academies and economists who professionally confront real world problems, either in private finance or in public policy. As economists we accept that the remarks made by Keynes in the closing passage of The General Theory are true: "... the ideas of economists and political philosophers, both when they are right and when they are wrong, are more powerful than is commonly understood. Indeed the world is ruled by little else. Practical men, who believe themselves to be quite exempt from any intellectual influences, are usually the slaves of some defunct economist. ....I am sure the power of vested interests is vastly exaggerated compared with the gradual encroachment of ideas. ... Soon or late it is ideas, not vested interests, which are dangerous for good or evil." We like this assertion not only because it makes us important but also because it makes good sense. The ideas that Keynes refers to are theories. A theory prior for rational action. A of system behavior is a proposed action, whether by individual agents in households or firms, a bank, a government agency or a legislative body is appropriate action only as a theory connects the action to the desired result. Because some institutions, such as deposit insurance, the savings and loan industry, and a number of the great private banks, that served the economy well during the first two generations after the great depression, seem to have broken down, the need to reform and to reconstitute the financial structure is now on the legislative agenda. As we try to fix the financial system three questions should be asked of the pushers of a policy proposal: 1. "What is it that is taken to be broke?", 2. "What theory about proposal?" 3. What are the dire consequences of not fixing that which you assert is broke? In what follows I will take up three points 1. Two views of the results of the economic process 2. Systemic and idiosyncratic sources of financial crises 3. Some ideas about the scope for policy in the present "crisis".
Keywords: 330